#TITLE_ALTERNATIVE# - (NIM 20506058), MUBAROH
Double salt of calcium copper(II) acetate hexahydrate, CaCu(CH3COO)4.6H2O has been synthesized from CaO in glacial acetic acid solution with copper(II) acetate solution, with mole ratio of Ca2+: Cu2+ was 4:1 and 6:1. The empirical formula of CaCu(CH3COO)4.6H2O was obtained from the elemental analysis of Ca = 8.62 % (8.93 %); Cu = 14.20 % (14.16 %); C = 21.67 % (21.45 %) and H = 5.90 % (5.40 %), the values on the bracket are based on the theoretical calculation. The salt showed paramagnetic properties with magnetic moment 1.75 BM. If the ratio of mole Ca2+: Cu2+ is less than 4:1 the simple salt of copper(II) acetate, Cu(CH3COO)2.H2O was produced. The elemental analysis for the simple salt are found for Cu = 31.87 % (31.72 %); C = 24.42 % (24.06 %) and H = 3.76 % (3.94 %). This salt has a dimeric structure with acetate ion as a bridge ligand. This salt also shows paramagnetic character with magnetic moment 1.86 BM, due to the existence of one free electron in the Cu2+ ion.